Heart rate response and contextual variables in professional rink hockey competitions - Fortunati, M.; Soldini, E.; Piccoli, M. B.; Lakicevic, N.; Crisafulli, O.; Drid, P.; Gemelli, T.; D`antona, G. (Medicina dello Sport, 2023)
BACKGROUND: Professional rink hockey is a highly demanding intermittent sport. This study investigates the heart rate response (HRR) during official rink hockey league matches and explores the influence of players` and match-related contextual variables on HRR. METHODS: Polar Team app was used to monitor heart rate. The variables extrapolated were time spent at <60%, 60-70%, 70-80%, 80-90%, and >90% of the maximum heart rate (HRmax) and relative HRmax. Multilevel regression models were used to explore the associations between dependent variables, player-, and match-related characteristics. Fifty-six matches during two regular seasons of the major league in a competitive-elite Italian rink hockey team were monitored. RESULTS: Overall, players spent ~40% of the time in the light intensity zones (<70% of HRmax), ~15% in the aerobic zone (70-80% HRmax), ~24% within the anaerobic zone (80-90% HRmax), and ~17-20% into the maximum effort zone (>90% HRmax). HRR was mainly related to training experience and the importance of each player within the team. In fact, starter players spend much more time at intensities >80% HRmax than first and second change players (P<0.001). CONCLUSIONS: In conclusion, starter players have a higher cardiovascular effort imposed by the match than first and second change players due to their primary role in the team. Therefore, we advise prescribing a weekly training plan based on the average HRR response for the players` category obtained during the competition to optimize recovery and reduce cumulative fatigue over the season.